Workforce optimization of a retail store - Özay, Ayşe. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
To decide optimal workforce composition according to fluxional demand is an important problem for retail stores in terms of customer satisfaction and also economical reasons. In this study, a combined decision making method is proposed for workforce optimization of a retail store. This method basically consists of two main stages. In the first stage, simulation model is developed for the retail store which is determined as a queueing network, and performance analysis is carried out. Scenarios containing different workforce compositions are created according to the output analysis of previous experiments. In the second stage, key performance measures identified in the first stage are employed as inputs into Weighted Goal Programming (WGP) model. By this integrated approach, not only dynamic in monthly basis but also stable workforce compositions can be selected among suggested scenarios. In WGP model employed in this proposed method, the weights of goal functions are derived using decision criteria weighting method of Analytic Hierarchy Process (AHP). Variability of these weights provides flexibility to the decision makers. In this study, the properties related to the customer satisfaction of simulation scenarios are also translated into qualitative terms for the purpose of easy evaluation by managers. In modeling this real-life problem, the actual constraints of the store and the desires of the managers are also taken into consideration.
Keywords: Personnel management.; Retail trade.